AMENTOFLAVONE FROM LEAVES OF NYAMPLUNG (Calophyllum inophyllum Linn.) - Wartono, M. Widyo; Wulandari, Dian; Handayani, Nestri; Suryanti, Venty; Marliyana, Soerya D. (Alchemy Jurnal Penelitian Kimia, 2012)
Amentoflavone (1), a biflavonoid was isolated from leaves of Calophyllum inophyllum Linn. Isolation and purification of the compound used maceration and chromatography methods using Si-gell and sephadex LH-20. The structure was determined by UV, IR, 1H and 13C NMR spectroscopy includes HMQC/HMBC analysis and comparison with references.